Fabrication of high-stability Ni-PSF@PAO40 microcapsules and their lubricating properties in polyamide 6 - Zhang, Wenli; Qi, Xiaowen; Yang, Xiao; Dong, Roger; Fan, Bingli; Liang, Lei (Springer, 2022)
Novel Ni-PSF@PAO40 microcapsules (NPPMS) with high stability were prepared by using a combined processing method of electroless nickel plating and solvent volatilization. The results indicate that Ni is completely assembled on the surfaces of PSF/PAO40 microcapsules with the encapsulation capacity of NPPMS achieved at 50%. Organic solvents immersion shows that NPPMS have an excellent chemical stability. Macro thermal stability tests reveal that the softening temperature of NPPMS is increased up to over 400 °C while it becomes lower than 200 °C for PSF/PAO40 microcapsules. Furthermore, NPPMS were embedded into polyamide 6 (PA6) to prepare PA6/NPPMS composites. The cross-sectional morphology shows that NPPMS are intact in PA6 matrices. The microhardness of PA6 is effectively improved with the incorporation of NPPMS. As compared with neat PA6, the coefficient of friction (COF) for PA6/NPPMS composites with 10% NPPMS could be reduced by 87.7% (from 0.49 to 0.06) and the wear rate could be decreased by 96.8% (from 1.29×10−⁵ to 4.15×10−⁷ mm³/(N·m)). Further studies confirmed that increasing test loads and test temperatures was beneficial to improve the lubrication performance of NPPMS despite the opposite trend occurred when increasing the sliding speeds. It has been demonstrated that synergistic effects between PAO40 and Ni layer play an important role in improving the tribological properties of PA6. Therefore, NPPMS significantly improve the ability of microcapsules to resist a harsh environment, which has important scientific significance for expanding the use of microcapsules more practically in self-lubricating composites.